A hierarchical scheduling method of active distribution network considering flexible loads in office buildings. (October 2021) - Li, Zening; Su, Su; Jin, Xiaolong; Chen, Houhe; Li, Yujing; Zhang, Renzun
Highlights: An energy consumption prediction model of the office building is proposed. A hierarchical scheduling method of the active distribution network is developed. The active distribution network under different control methods is analyzed. The results under different weights and building permeabilities are investigated. Abstract: Aiming to further achieve the flexible operation of the active distribution network by utilizing heating, ventilation and air-conditioning systems and electric vehicles of office buildings, a hierarchical scheduling method of active distribution network considering flexible loads in office buildings is proposed in this paper. In stage I, based on the heat storage property of office buildings and the behavioral property of office workers, an energy optimal scheduling model of the office building incorporating heating, ventilation and air-conditioning systems and electric vehicles is established. In stage II, an optimal scheduling method of the active distribution network considering on-load tap changer and flexible loads (i.e., heating, ventilation and air-conditioning systems and electric vehicles) in office buildings is developed by using the second-order conic relaxation and piecewise linearization. Finally, the scheduling results for the heating, ventilation and air-conditioning systems and electric vehicles in office buildings under different cases are compared in a winter scenario, and the security and economy of the active distribution network considering flexible loads in office buildings are further analyzed. Numerical studies demonstrate that the proposed method can contribute to the office building cost reduction and the load factor increment while guaranteeing the heating and the transportation demands of office workers. It can further improve the security and economic operation of the distribution network.